Development of an automatable method for the measurement of endo-1, 4-β-xylanase activity in barley malt and initial investigation into the relationship between endo-1, 4-β-xylanase activity and wort viscosity. (November 2018) - Mangan, David; Cornaggia, Claudio; Liadova, Agnija; Draga, Anna; Ivory, Ruth; Evans, D. Evan; McCleary, Barry V.
Abstract: Stages of the brewing process, such as mash separation to produce wort and beer filtration, can in certain cases prove problematic due to the increased viscosity caused by high levels of the non-starch polysaccharides, primarily β-glucan and arabinoxylan. Of these two polysaccharides, β-glucan has been extensively studied, but arabinoxylan has been somewhat overlooked. The concentration of arabinoxylan present during these process stages is principally expected to be inversely related to the malt endo -1, 4-β-xylansase activity that is available to degrade these polysaccharides. The development of a novel method for the measurement of endo -1, 4-β-xylansase activity in barley malt extracts is described herein. The method was characterised by two analysts in terms of repeatability (single analyst CVs = 2.2% and 2.3%, n = 8; interanalyst CV = 4.8%, n = 16) and sensitivity (LOD = 10 U/kg, LOQ = 34 U/kg). The assay procedure was then applied to the measurement of xylanase activity in a series of eight standard barley malts and the results obtained were compared with their associated Congress wort viscosities as measured using the conventional EBC Method 4.8, wort viscosity. A highly statistically significant relationship between xylanase activity and wort viscosity was found with a Pearson's correlation coefficient of −0.82 ( p -value of 0.007). Highlights: Optimised extraction procedure developed for endo -1, 4-β-xylanase in barley malt. Automatable colorimetric assay procedure was developed for use with malt extracts. Assay principle based on the b-xylosidase coupled assay involving XylX6 substrate. LOD (10 U/kg), LOQ (34 U/kg) and CV (2.2–4.8%) were calculated for the new method. Correlation observed (−0.82, p = 0.007) between xylanase activity and wort viscosity.